Efektifitas Pengisian Baterai Menggunakan Solar Panel 50 WP (Watt Peak) dengan Metode PWM (Pulse Width Modulation) - Ikhwan Mustiadi; Evrita Lusiana Utari (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2023)
Electrical energy has become a basic need for humans today, almost all aspects of human life require electrical energy. The electrical energy needed so far has been produced from fossil energy which is not environmentally friendly and has dwindling reserves, alternative energy is needed which is environmentally friendly and sustainable. Energy that can be utilized includes water energy, wind energy, solar energy and so on. The sun is one of the abundant energy, by crossing the equator, Indonesia has enormous energy reserves. This potential is expected to become Indonesia's future energy. Currently solar cell technology is very advanced with increasingly good efficiency, in addition to energy conversion by solar cells with photovoltaic technology, a method is needed to store the results of the conversion into storage (batteries) optimally. One of the battery charging technologies is the Pulse Width Modulation (PWM) method, with this method battery charging is optimal on a 50 WP solar panel. In this study, a 50 WP solar panel was used, a 28 Ah 12 Volt battery, a 10 Watt Dc 12 Volt load and a 10 Ampere PWM Solar Charger Controller (SCC). The system was running for 3 months from September to December, the load was turned on for 12 hours every day with a load absorption current of 0.9 Amperes. Every day the current used is 10.8 Amperes. For 3 months the weather was not always stable, so charging was less than optimal, but until now the system is running well with an average after usage voltage of 12.3 Volts.